Kewenangan Pemerintah Daerah Dalam Penertiban Orang Dengan Gangguan Jiwa - Talaksoru, Derek; Pietersz, Jemmy Jefry; Soplanit, Miracle (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2025)
Mental disorders are conditions that require serious attention and handling by the government. Local governments have the authority to address mental health issues, but this authority still needs to be clarified and accounted for. The problem of mental disorders is a health issue that requires special and continuous handling. Local governments play an important role in ensuring effective and humane treatment of people with mental disorders (ODGJ), in accordance with applicable laws and regulations. The research method used is normative juridical. It employs problem approaches such as conceptual approaches and legal regulations approaches. The legal sources used include primary, secondary, and tertiary legal materials. The collection of legal materials is conducted through literature studies, which are then analyzed qualitatively. The research findings indicate that local governments have full authority to regulate ODGJ in public facilities; however, the implementation of policies in the field has not been optimal. This is due to the inconsistency of the government in regulating ODGJ in public facilities, a lack of trained human resources, and the negative stigma toward ODGJ in society. The study also finds that coordination among local governments, relevant agencies (such as the Social Service and Health Department), and the community needs to be improved to ensure proper and sustainable handling. Local governments also need to strengthen their capacity and coordination in the regulation and management of ODGJ.